2022
DOI: 10.3389/fnut.2022.940841
|View full text |Cite
|
Sign up to set email alerts
|

Association of sugar-sweetened beverages with executive function in autistic children

Abstract: The association between sugar-sweetened beverages (SSBs) consumption and executive function (EF) among typically developing (TD) children has been investigated in previous studies but with inconsistent results. Furthermore, this relationship has been less investigated among autistic children who perform worse in EF compared with TD children. In this study, we aimed to investigate the association between SSB consumption and EF in autistic children, and whether the association between SSB and EF in autistic chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…Among them, 45 million are from China, which would place China the second largest number of children with cognitive delay in the world (4)(5)(6). Previous studies have shown that delayed cognitive development affects the academic performance and mental health of children, such as an increased risk of attention deficit hyperactivity disorder and emotional symptoms (7). Maintaining the healthy development of cognitive function has emerged as an important public health issue in children.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, 45 million are from China, which would place China the second largest number of children with cognitive delay in the world (4)(5)(6). Previous studies have shown that delayed cognitive development affects the academic performance and mental health of children, such as an increased risk of attention deficit hyperactivity disorder and emotional symptoms (7). Maintaining the healthy development of cognitive function has emerged as an important public health issue in children.…”
Section: Introductionmentioning
confidence: 99%
“…In China, snacks and SSBs consumption is very common among preschool children (23)(24)(25). However, previous studies have only focused on the effects of SSB consumption on cognitive function (7,26). To our knowledge, the effects of other ultraprocessed food consumption on children's cognition function are rarely discussed.…”
Section: Introductionmentioning
confidence: 99%